Dogmatic landmarks in Russian and Romanian iconography The Icon of the Holy Trinity - Mohor-Obreja, Bogdan (Technium Social Sciences Journal, 2023)
The mystery of the Most Holy Trinity of one being represents the basis of our Christian faith and living, at the same time being the living soul of the Church, which it makes live from the triune life, graciously shared with all its members, in an endless kenosis of love, which elevates, perfects and deifies.